Effect of fermentation on anthocyanin stability and in vitro bioaccessibility during shalgam (şalgam) beverage production. (15th February 2018) - Toktaş, Betül; Bildik, Fatih; Özçelik, Beraat
Abstract: BACKGROUND: Shalgam is a traditional lactic acid fermented beverage highly popular in southern Turkey. The main raw material, black carrot, contains a significant amount of anthocyanins. In this study, changes in polyphenols, including anthocyanins, related total antioxidant capacity (TAC), and in vitro bioaccessibility during shalgam fermentation and main raw material were evaluated. RESULTS: Compared with the last 12 days of the fermentation, a higher increase in total phenolic content (TPC), anthocyanins content (AC), and TAC was observed in the first 12 days of the fermentation during shalgam production. Although black carrot exhibited the highest total flavonoid content (TFC), TPC, AC, and TAC values before bioaccessibility tests, the recovery of shalgam beverage was found to be mostly identical with black carrot results in terms of flavonoids, phenolics, and anthocyanins and antioxidant capacity after in vitro digestion. In vitro digestion significantly reduced the recovery of initial samples in terms of TFC, TPC, AC, and TAC analysis. The amount of beneficial compound in the early fermentation stage was significantly lower than with end product. Sixteen different phenolics were detected from shalgam beverage samples in high‐performance liquid chromatography analysis. After performing bioaccessibility tests, only five phenolics were detected. As anthocyanins, only cyanidin content was identified. CONCLUSION: The degradation of phenolics and anthocyanins was observed after bioaccessibility tests. © 2017 Society of Chemical Industry